Democratic consolidation in Eastern Europe. - Zielonka, Jan, 1955- (Oxford studies in democratization., 2001)
This collection of papers is part of a series on democratic consolidation in post-communist Central and Eastern Europe. This first volume analyses constraints on and the opportunities provided by institutional engineering.